Electro-precipitation of Fe(3)O(4) nanoparticles in ethanol - Marques, Rodrigo Fernando Costa [UNESP]; Garcia, Cecile; Lecante, Pierre; Ribeiro, Sidney José Lima [UNESP]; Noe, Laure; Silva, Nuno J. O.; Amaral, Vitor S.; Millan, Angel; Verelst, Marc (Elsevier B.V., 2008)
The preparation of superparamagnetic magnetite (Fe(3)O(4)) nanoparticles by electro-precipitation in ethanol is proposed. Particle average size can be set from 4.4 to 9 nm with a standard deviation around 20%. Combination of wide-angle X-ray scattering (WAXS), Electron energy loss spectroscopy (EELS) and Mossbauer spectroscopy characterizations clearly identifies the particles as magnetite single-crystals (Fe(3)O(4)). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: nanoparticle; magnetite; magnetic material; iron oxide